2011
DOI: 10.14710/jitaa.36.2.97-103
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF ORGANIC-Cr DIETARY SUPPLEMENTATION ON STRESS RESPONSE IN TRANSPORT-STRESSED BEEF CATTLE

Abstract: Transportation over long distances resulted in stress at animal. Under these circumstances, animal usually manifest depression and the impact on physiological condition changes and loss of body weight. The objectives of the research were to examine effect supplementation of organic-Cr type into diets in transport-stress beef cattle on physiological condition, haematochemical (included were haematological condition and blood chemical) and body weight changes. The experiment was conducted using 16 beef cattle th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
0
13
0
4
Order By: Relevance
“…The productivity of duckweed is high, ie every two days biomass is produced once as initial biomass, if regulated effectively it can produce 10-30 tons of dry matter.ha -1 .year -1 with a content of 43% crude protein (Sasmaz et al 2015;Lai et al 2016). The results of the study by Ippolito et al (2014) showed that the productivity of duckweed biomass was about 176.38 g/m 2 in wet conditions or 6.24 g.m 2 in dry conditions, whereas the results of studies in the Cikajang Garut area, the productivity of duckweed around 234.37 g.m 2 in a wet state (Tanuwiria et al 2011). Based on the high protein content, duckweed has potential as a feed ingredient.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The productivity of duckweed is high, ie every two days biomass is produced once as initial biomass, if regulated effectively it can produce 10-30 tons of dry matter.ha -1 .year -1 with a content of 43% crude protein (Sasmaz et al 2015;Lai et al 2016). The results of the study by Ippolito et al (2014) showed that the productivity of duckweed biomass was about 176.38 g/m 2 in wet conditions or 6.24 g.m 2 in dry conditions, whereas the results of studies in the Cikajang Garut area, the productivity of duckweed around 234.37 g.m 2 in a wet state (Tanuwiria et al 2011). Based on the high protein content, duckweed has potential as a feed ingredient.…”
Section: Introductionmentioning
confidence: 98%
“…Application of natural matter as feed mixes has been reported in animals. The potential use of duckweed (Lemna minor) feed ingredients is supported by the high protein content which ranges from 22.40%, crude fiber 10.16% (Sasmaz et al 2015), and its metabolic energy reaches 2342 kcal.kg-1 dry matter, amino acids especially lysine reached 6.9 g in 100 g, methionine 1.4%, and histidine 2.7% (Tanuwiria et al 2011), and rich in minerals and vitamin A (Saygideger et al 2015), also amino acid microminerals (Sazmaz et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the level of these intermediates occurs due to an increase in glycogenolysis. Previous research also showed an increased profile of intermediate metabolites with the same profile (Tanuwiria et al 2011;Gray et al 2015;Mingoti et al 2016;Siskos et al 2017).…”
Section: Glycogenolysis Pathwaymentioning
confidence: 73%
“…The metabolic activity has an impact on liver cells, and causes oxidative damage to lipids and lipoproteins, which are components of cells (Tanuwiria, 2011;Vizzoto et al 2015). Several studies have shown that oxidative damage causes the emergence of free radicals, which in turn, damages lipid structure (Tian et al 2016;Damaziak et al 2017;Hernawan et al 2017), enzymes (Burdick et al 2011), nucleic acids and proteins (Carrol et al 2016) as well as cell and DNA damage (Cai et al 2014;Shin et al 2010;Holt et al 2019).…”
Section: Plasma Biochemistrymentioning
confidence: 99%
“…Pada penambahan Cr dalam diet, sebaiknya dalam bentuk organik karena tidak toksik dan dapat dapat diabsorbsi dengan baik oleh tubuh (25-30%). Penambahan Cr dalam diet berguna terutama untuk meningkatkan imunitas dan mengurangi stres hewan selama transportasi (Tanuwiria et al 2011). Penambahan Cr organik selama pertumbuhan dalam periode penggemukan sapi sebanyak 0,2 ppm terbukti dapat meningkatkan berat karkas yaitu 315 kg, sedangkan karkas kontrol tanpa penambahan Cr organik 302 kg (Pollard et al 2002).…”
Section: Rhizopus Sp Meningkatkan Kualitas Nutrisi Pakan Ternakunclassified